EX VIVO MODEL FOR THE CHARACTERIZATION AND IDENTIFICATION OF DRYWALL INTRAOCULAR FOREIGN BODIES ON COMPUTED TOMOGRAPHY. Issue 7 (July 2018) - Syed, Reema; Kim, Sung-Hye; Palacio, Agustina; Nunery, William R.; Schaal, Shlomit
Abstract : Background: The study was inspired after the authors encountered a patient with a penetrating globe injury due to drywall, who had retained intraocular drywall foreign body. Computed tomography (CT) was read as normal in this patient. Open globe injury with drywall has never been reported previously in the literature and there are no previous studies describing its radiographic features. Methods: The case report is described in detail elsewhere. This was an experimental study. An ex vivo model of 15 porcine eyes with 1 mm to 5 mm fragments of implanted drywall, 2 vitreous only samples with drywall and 3 control eyes were used. Eyes and vitreous samples were CT scanned on Days 0, 1, and 3 postimplantation. Computed ocular images were analyzed by masked observers. Size and radiodensity of intraocular drywall were measured using Hounsfield units (HUs) over time. Results: Intraocular drywall was hyperdense on CT. All sizes studied were detectable on Day 0 of scanning. Mean intraocular drywall foreign body density was 171 ± 52 Hounsfield units (70–237) depending on fragment size. Intraocular drywall foreign body decreased in size whereas Hounsfield unit intensity increased over time. Conclusion: Drywall dissolves in the eye and becomes denser over time as air in the drywall is replaced by fluid. This study identified Hounsfield Units specific to intraocular drywall foreign body over time. Abstract : This is the first study to establish an ex vivo model to investigate the computed tomography characteristics of drywall foreign bodies. Intraocular drywall foreign body was hyperdense on computed tomography and became denser as it dissolved in the eye over time.